Comparative Analysis of Reactive Protocols in Mobile Ad-Hoc Networks - Mannan, Nisha; Khurana, Shipra (International Journal of Computer Sciences and Engineering, 2014)
MANETs have three types of routing protocols, Reactive protocols, Proactive protocols and Hybrid Protocols. The routing protocols designed majorly for internet are fundamentally different from the mobile Ad-Hoc networks (MANET). In research community very little attention has been given towards performance issues in MANET. This review focuses on MANETs focused mainly on comparing different reactive protocols or proactive protocols.